Supervisi Kepala Sekolah dalam Pengembangan Keprofesian Berkelanjutan Guru: Studi Kualitatif di SMAN 1 Pabelan - Winarsa, Raden Daru Murti Tri; Supriadi, Didi; Purbonuswanto, Welius (Media Manajemen Pendidikan, 2025)
This research aims to find out how sustainable professional development is implemented at SMAN 1 Pabelan, find out the supporting and inhibiting factors that influence sustainable professional development, find out what the Principal has done as a supervisor in supporting continuous professional development for teachers, find out the results of the role The principal has acted as a supervisor for teachers in implementing CPD. The type of research is qualitative. The research subjects were the principal and 20 teachers. Using triangulation of data sources, through interviews, observation and documentation, the data analysis technique that will be used is interactive model analysis. The results of the research were that the principal carried out several stages, namely planning supervision, implementing supervision, and evaluating supervision. The supervision approaches used are direct and indirect approaches. The supervision techniques used are class visits, individual conferences, teacher/staff council meetings, inter-school visits, inter-class visits, meetings in working groups\MGMP, and seminars. Supervision results increase teacher professionalism in pedagogical competence, personality competence, professional competence and social competence.